In Medias Res: Deleuze and the Politics of Middleness - Pendakis, Andrew (Stasis, 2019)
This paper explores the links between the work of Gilles Deleuze and two tropes of middleness, both of which are central to the reproduction of neoliberalism. The middle in neoliberal (or postmodern) societies is a key tropological, given first as an explicit political imaginary, what I call the “radical centre,”and second, in the form of a background ontology I call “universal middleness.” Though this essay does not argue that Deleuze is even remotely a centrist in disguise, it does claim that a worrying resonance exists between too-fast readings of his work and the ambient middles invoked above. When not properly theorized, the givenness of these ideologies of the middle ends up spontaneously reproducing the common sense of neoliberalism; this is a danger too for those readings of Deleuze that subtract from his work its radical anti-capitalist core and instead read him as a pure ontologist (of the middle) or as a post-ideological ethicist of the in-between.